The role of online translation tools in language education - Kučiš, Vlasta; Seljan, Sanja (2013)
The aim of the pilot study is to draw attention to the importance of online translation tools as a contemporary didactic tool in the language and translation educational process. In the paper the following hypotheses were tested: i) use of free online translation tools can contribute to the development of ICT competences ; ii) use of modern translation tools contribute to the consistency and quality ; iii) free online translation tools for under-resourced languages can be used as pedagogical tools. Two studies were conducted using the text of EU legislation (acquis communautaire). In the first study, evaluation of the German-Slovenian translation quality of legislation was performed between two groups: one group using traditional reference works and the other group using online electronic translation tools (the Slovenian multilingual terminology database Evroterm and the bilingual corpus Evrokorpus). In both translations, mistakes were analyzed and a paired samples t-test was conducted. In the second study, machine translation of English-Croatian legislative text using the Google Translate online translation service was analyzed. The human evaluation of the translation quality was calculated, and Fleiss' kappa metric used to assess inter-rater reliability of agreement. The evaluation was enriched by analysis of different types of errors.
Projekt MZOS
ENG